Aerobic exercise attenuates pulmonary injury induced by exposure to cigarette smoke - Toledo A.C. (2012)
It has recently been suggested that regular exercise reduces lung function decline and risk of chronic obstructive pulmonary disease (COPD) among active smokers; however, the mechanisms involved in this effect remain poorly understood. The present study evaluated the effects of regular exercise training in an experimental mouse model of chronic cigarette smoke exposure. Male C57BL/6 mice were divided into four groups (control, exercise, smoke and smoke+exercise). For 24 weeks, we measured respiratory mechanics, mean linear intercept, inflammatory cells and reactive oxygen species (ROS) in bronchoalveolar lavage (BAL) fluid, collagen deposition in alveolar walls, and the expression of antioxidant enzymes, matrix metalloproteinase 9, tissue inhibitor of metalloproteinase (TIMP)1, interleukin (IL)-10 and 8-isoprostane in alveolar walls. Exercise attenuated the decrease in pulmonary elastance (p<0.01) and the increase in mean linear intercept (p=0.003) induced by cigarette smoke exposure. Exercise substantially inhibited the increase in ROS in BAL fluid and 8-isoprostane expression in lung tissue induced by cigarette smoke. In addition, exercise significantly inhibited the decreases in IL-10, TIMP1 and CuZn superoxide dismutase induced by exposure to cigarette smoke. Exercise also increased the number of cells expressing glutathione peroxidase. Our results suggest that regular aerobic physical training of moderate intensity attenuates the development of pulmonary disease induced by cigarette smoke exposure. Copyright©ERS 2012.